Decoding Worldwide Trends on Cooperatives and their Economic Influence: A Bilbliometric Analysis from 2015-2025 - Muchammad Shubchi Fadhilah Ramadhan; Hamdan Ardiansyah (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
Cooperatives play a crucial role in global economic development, contributing to financial stability, employment creation, and sustainable business practices. This study examines research trends on cooperatives using bibliometric analysis and a systematic literature review, focusing on key themes such as governance, economic resilience, and digital transformation. Findings indicate that cooperatives significantly contribute to GDP and job creation while demonstrating resilience during financial crises. Their role in sustainability is also expanding, with cooperatives driving environmentally friendly initiatives in various sectors. However, challenges such as regulatory constraints, market competition, and digital adaptation persist. Differences in legal frameworks hinder cooperative expansion, and limited technological resources slow digital transformation. To address these issues, stronger policies, financial support, and technological integration are needed. This study underscores the increasing importance of cooperatives in fostering economic resilience and sustainability while emphasizing the need for continued research on innovation and global collaboration to enhance cooperative effectiveness.